Display of sign the "productivity" and its elements at the collection of millet samples of different ecological and geographical origin in the conditions of South Forest-Steppe of Ukraine - Холод, С. Г. (Scientific Progress & Innovations, 2012)
The results of three-year study of collection set of millet samples, different originally (from 34 countries of the world) and to biological status (local and plant-breedings varieties, lines) on a sign the "productivity" and to its making elements in the contrasting weather terms of growing are resulted in the article. The coefficients of variation and level of cross-correlation connections are certain between these indexes. It is set that most productive were samples by an origin from Ukraine, Japan, India, Morocco and France. 20 high-yield samples of millet are selected with a stable index on years, which are recommended as a initial material for a selection on stabilizing of the productivity.